Razvoj elementov internacionalizacije univerze skozi čas - Potočnik Mesarić, Tanja (Šolsko polje, 2016)
The basic building blocks of the internationalization of universities which arose throughout history are identified in this article. We identified the following elements of the internationalization with the comparative historical method: mobility of students, mobility of academic staff, a common teaching language, accreditation, uniform curriculum, the export of higher education systems and dissemination of researches. Historical elements have more or less power during the historical social events and have expressed varying degrees. Closed nation states that emerged in the first half of the 19th century have limited elements the most, and after the peak of nationalism with World War II, the elements were once again brought to life by encouraging social circumstances for internationalization (globalization). Elements were linked to various forms of internationalization acoording to Jane Knight's theory (2007b) at the end of the article. Historical elements of internationalization are the basic building blocks of every form of internationalization. Due to the loaded burdens on university caused by the environment (institutional differentiation, the emergence of new disciplines, nationalism, market mechanisms and the massification), we can not simply revive the Middle Ages, but we need to carefully introduce each element taking into account the current environment and the accumulated historical heritage.
Keywords: Šolsko polje; The School field; vzgoja in izobraževanje; education; university; univerza; internacionalizacija univerz; internationalization; historical elements; oblike internacionalizacije; nacionalna država; nation-state; mobility; mobilnost; re-internacionalizacija univerz; re-internalization; historični elementi